El presidente de la república tendrá la posibilidad de delegar funciones en los estados de excepción,siendo para esto necesario reformar el capítulo II del título VI de la ley de seguridad pública y del estado - Franco Trujillo, Christian Renato (2016)
The issue I set out to develop titled "THE PRESIDENT OF THE REPUBLIC OF DELEGATION WILL HAVE THE POSSIBILITY FUNCTIONS IN THE STATES OF EXCEPTION BEING NECESSARY FOR THIS CHAPTER II REFORMING THE TITLE VI OF THE LAW OF PUBLIC SAFETY AND STATE" so I would make the summary. This research work aims to analyze the conceptual, doctrinal framework; and law of the Constitution of the Republic of Ecuador; and the Public Security Act and the State regarding states of emergency; and determine the need for the Public Safety Act and the State, provides power to delegate powers to the President of the Republic only in cases of emergency. With this research work intend to incorporate in the Law of Public Security and the State, the articles necessary to provide the aforementioned legal sufficient rules intended to empower the delegation of functions by the Head of State in the cases where decreed a state of emergency, that given that this circumstance has not been foreseen in the Law of Public Security and the State; and I think that is a legal and viable alternative to resolve the internal conflicts that can severely shock the State; and that its gravity requires emergency decree; circumstances which will enable not only safeguard the security of the Head of State; but also you get down the degree of discomfort between the executive; and groups or organizations that led to the declaration of a state of emergency; which would allow our country more quickly return to normal activities, a fact that should be provided expressly in the Law of Public Security and the State, through the determination not only of the power to delegate tasks, but also determining Where this would be feasible to delegate authority and administrative procedure to be followed for the purpose. From the foregoing I consider that by studying the structure of our state, legally analyze the functions of head of state and the relationship between other functions, as well as about the characteristics surrounding the state of emergency, may formulate a viable legal proposal contribute to improving the current legislation; and above all in his application considered safeguard internal security of our country.